Stroke Incidence by Major Pathological Type and Ischemic Subtypes in the Auckland Regional Community Stroke Studies: Changes Between 2002 and 2011. Issue 1 (January 2018) - Krishnamurthi, Rita V.; Barker-Collo, Suzanne; Parag, Varsha; Parmar, Priyakumari; Witt, Emma; Jones, Amy; Mahon, Susan; Anderson, Craig S.; Barber, P. Alan; Feigin, Valery L.
Abstract : Background and Purpose—: Major pathological stroke types (ischemic stroke [IS], primary intracerebral hemorrhage [ICH], and subarachnoid hemorrhage) and IS subtypes, have differing risk factors, management, and prognosis. We report changes in major stroke types and IS subtypes incidence during 10 years using data from the ARCOS (Auckland Regional Community Stroke Study) III performed during 12 months in 2002 to 2003 and the fourth ARCOS study (ARCOS-IV) performed in 2011 to 2012. Methods—: ARCOS-III and ARCOS-IV were population-based registers of all new strokes in the greater Auckland region (population aged >15 years, 1 119 192). Strokes were classified into major pathological types (IS, ICH, subarachnoid hemorrhage, and undetermined type). Crude annual age-, sex-, and ethnic-specific stroke incidence with 95% confidence intervals was calculated. ISs were subclassified using TOAST (Trial of ORG 10172 in Acute Stroke Treatment) criteria into 5 etiologic groups. Rate ratios with 95% confidence intervals were calculated for differences in age-standardized rates between the 2 studies. Results—: In ARCOS-IV, there were 1329 (81%) ISs, 211 (13%) ICHs, 79 (5%) subarachnoid hemorrhages, and 24 (1%) undetermined type strokes. The proportional distribution of IS subtypes was 29% cardioembolism, 21% small-vessel occlusion, 15% large-artery atherosclerosis, 5% other determined etiology, and 31% undetermined type. Between 2002 and 2011, age-standardized incidence decreased for subarachnoid hemorrhage (rate ratios, 0.73; 95% confidence intervals, 0.54–0.99) and undetermined type (rate ratios, 0.14; 95% confidence intervals, 0.09–0.22). Rates were stable for IS and ICH. Among IS subtypes, large-artery atherosclerosis and small-vessel occlusion rates increased significantly. The frequency of all risk factors increased in IS. Ethnic differences were observed for both stroke subtype rates and their risk factor frequencies. Conclusions—: A lack of change in IS and ICH incidence may reflect a trend toward increased incidence of younger strokes. Increased rates of large-artery atherosclerosis and small-vessel occlusion are associated with increased smoking and high blood pressure. Ethnic differences in the proportional distribution of pathological stroke subtypes suggest differential exposure and susceptibility to risk factors. Abstract : Supplemental Digital Content is available in the text.